RELATIVITY OF ACCOUNTING VALUES: CAUSES, CONSEQUENCES AND LIMITATION POSSIBILITIES - Mihaela Enachi; Daniel Botez (Studies and Scientific Researches: Economics Edition, 2021)
Accounting is influenced by a variety of historical, economic, cultural, and other non-accounting factors that led to different judgments in creating a system for representing the reality, the application of regulated requirements and the validation of the fidelity of the information in the annual financial statements, as a final product of accounting. In this article, we focus on the main determinants of the relativity of the values that characterize the events in the life of an organization, which can determine the different reporting of similar realities. Thus, we focus on the influence of taxation on accounting, on accounting policies and management decisions and the professional judgment in forming an opinion on the financial statements and we try to identify solutions to limit the relativity of the accounting values.